2010
DOI: 10.1186/1477-7819-8-89
|View full text |Cite
|
Sign up to set email alerts
|

Association between intratumoral lymphatic microvessel density (LMVD) and clinicopathologic features in endometrial cancer: a retrospective cohort study

Abstract: BackgroundLymph node metastasis in endometrial cancer significantly decreases survival rate. Few data on the influence of intratumoral lymphatic microvessel density (LMVD) on survival in endometrial cancer are available. Our aim was to assess the intratumoral LMVD of endometrial carcinomas and to investigate its association with classical pathological factors, lymph node metastasis and survival.MethodsFifty-seven patients with endometrial carcinoma diagnosed between 2000 and 2008 underwent complete surgical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(29 reference statements)
1
7
0
2
Order By: Relevance
“…Therefore, lymph vessels were counted in the tumor invasive front, considered most crucial for malignant cell spread [35]. The range of lymph vessels determined in our study was in accord with previous reports [36,37]. Consistent with our results, increased LVD has been correlated with a dense infiltration of TAMs in a number of cancer entities [38].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, lymph vessels were counted in the tumor invasive front, considered most crucial for malignant cell spread [35]. The range of lymph vessels determined in our study was in accord with previous reports [36,37]. Consistent with our results, increased LVD has been correlated with a dense infiltration of TAMs in a number of cancer entities [38].…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that D2-40 is the most sensitive and specific antibody for the detection of lymphatic endothelium in different malignancies like gastric [19], colorectal [20], vulvar [21], breast [22] and endometrial cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous experience with cancers of the vulva, cervix and endometrium, we found an inverse correlation between intratumoral LVD and lymph node metastasis and prognosis 9-11. To explain our previous results, we hypothesized that the intratumoral lymphatic vessels were non-functional and therefore had the potential to disturb local drainage, including the transport of neoplastic cells outside the tumor.…”
Section: Discussionmentioning
confidence: 79%